2022
DOI: 10.1002/iub.2616
|View full text |Cite
|
Sign up to set email alerts
|

Herbal inhibitors of SARS‐CoV‐2 Mpro effectively ameliorate acute lung injury in mice

Abstract: Coronavirus disease 2019, a newly emerging serious infectious disease, has spread worldwide. To date, effective drugs against the disease are limited. Traditional Chinese medicine was commonly used in treating COVID‐19 patients in China. Here we tried to identify herbal effective lipid compounds from the lipid library of 92 heat‐clearing and detoxication Chinese herbs. Through virtual screening, enzymatic activity and inhibition assays, and surface plasmon resonance tests, we identified lipid compounds targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Lysophosphatidylcholine (16:0/0:0) ( Figure 7A ), which is present in the phospholipid biosynthesis pathway, was also significantly increased. It has been confirmed to alleviate lung injury of acute respiratory distress syndrome by down-regulating the mRNA expression of inflammatory factors such as TNF-α, IL-6, and IL-1β, as well as by reducing neutrophil infiltration ( Du et al, 2022 ). This suggests that lysophosphatidylcholine (16:0/0:0) has certain anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Lysophosphatidylcholine (16:0/0:0) ( Figure 7A ), which is present in the phospholipid biosynthesis pathway, was also significantly increased. It has been confirmed to alleviate lung injury of acute respiratory distress syndrome by down-regulating the mRNA expression of inflammatory factors such as TNF-α, IL-6, and IL-1β, as well as by reducing neutrophil infiltration ( Du et al, 2022 ). This suggests that lysophosphatidylcholine (16:0/0:0) has certain anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Lysophosphatidylcholine (16:0/0:0) (Figure 7A), which is present in the phospholipid biosynthesis pathway, was also significantly increased. It has been confirmed to alleviate lung injury of acute respiratory distress syndrome by down-regulating the mRNA expression of inflammatory factors such as TNF-α, IL-6, and IL-1β, as well as by reducing neutrophil infiltration (Du et al, 2022). This suggests that lysophosphatidylcholine (16:0/0:0) has certain antiinflammatory effects.…”
Section: Discussionmentioning
confidence: 94%
“…The NDF content of silage was reduced (p < 0.05) with the LP + LB treatments. Similarly, Du et al (2022) reported that the content of NDF in ryegrass silage inoculated with L. plantarum, L. buchneri and L. casei was reduced after 60 days of ensiling. When ensiled for 30 days, the PA and LP + PA treatments had a lesser (p < 0.05) NDF content than CK.…”
Section: Nutritional Quality Of Hybrid Pennisetum Silagementioning
confidence: 85%
“…Severe cases can develop into acute respiratory distress syndrome (ARDS), with a mortality rate of 30–40% (Guo et al, 2021; Wang, Sun, et al, 2021). Under the novel coronavirus pneumonia (COVID‐19) situation, ARDS caused by ALI has emerged as a global public health problem (Du et al, 2022). Currently, mechanical ventilation and glucocorticoids are used in clinical practice to treat patients with ALI (Diaz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%